Potret Kebahagiaan Relawan Studi Kasus Relawan Satya Wacana Peduli di Lombok - Joshua Jordan Karinda; Rudangta Arianti (Universitas Kristen Maranatha, 2020)
The main purpose of all activities carried out by humans is to obtain happiness. The same thing happened to Satya Wacana Peduli volunteers who provided assistance directly to the people in Lombok. The purpose of this study is to see a picture of happiness in volunteers who were members of Satya Wacana Peduli. This research was analyzed qualitatively by using a case study approach. The study involved two volunteers who provided assistance in Lombok. The results of the study showed that the picture of happiness in each participant was different. The difference in happiness was influenced by the initial encouragement of participants to provide assistance. The suggestion for the next research is to pay more attention to factors that influence happiness such as personality factors or other factors that make volunteers can feel happiness. Keywords: happiness, volunteer, qualitative.